PERFORMA PERTUMBUHAN UDANG WINDU (Penaeus monodon) YANG DIBUDIDAYAKAN BERSAMA RUMPUT LAUT (Gracilaria sp.) DENGAN PADAT TEBAR YANG BERBEDA MENERAPKAN SISTEM INTEGRATED MULTI-TROPHIC AQUACULTURE (IMTA) - Sri Rejeki; Restiana Wisnu Aryati; Irma Azizah (Departemen Akuakultur FPIK UNDIP, 2018)
Tiger shrimp is a commodity pond that has high economic value compared to others. Tiger shrimp culture can be done by using a monoculture system, a polyculture system or an Integrated Multi-trophic Aquaculture (IMTA) system. IMTA system is one solution to reduce the environmental impact of cultivation activities because undigested feed and metabolism results in an accumulation of feces in the pond. This study aims to determine the effect of the addition of seaweed into the system on the growth and survival rate of tiger shrimp and also to determine the best density of seaweed in controlling the water quality. The research was conducted from September 2017 to November 2017 in Tambak Bulusan Village, Demak, Central Java. The material used is seaweed. Tiger shrimp used in size PL 30 measuring 2.0-2.9 cm. In length the stocking density is 80 individuals/m. The feed used is pellets given by using a fixed feeding rate of 5%. This research used an experimental method with complete randomized design with 5 treatments and 3 replications. The treatment of seaweed stocking used is 50 g, 100 g, 150 g, and 200 g. The results showed that different stocking of seaweed had significant effect on growth of weight, relative growth rate, survival rate of tiger shrimp. The best treatment of seaweed density is treatment A1 (50 gram), treatment A1 can increase the value of tiger shrimp growth with absolute weight of 1.67 ± 0.05 gram; the relative growth rate of 36.36 ± 1.04 %; and the survival rate of 78.75 ± 1.25 %. While the best growth value of seaweed is at treatment A1 (50 gram) with weight growth value of 73,21 ± 4,26 gram, and daily growth rate of 2,15 ± 0,08 %/day. Seaweed can balance the quality of waters with the results of nitrate water quality of 0.02 mg / L - 0.08 mg / L, nitrites of 0.00 - 0.42 mg / l, and ammonia levels of 0.02 - 0.59 mg / l. The results are quite feasible for shrimp farming activities.Keywords: growth, Penaeus monodon, Gracilaria sp., IMTA